On the number of connected and disconnected coverings over a manifold - Liskovets, Valery A. (Ars mathematica contemporanea, 2009)
A general formula is obtained for the number of non-equivalent coverings (possibly disconnected) over a connected manifold with an arbitrary finitely generated fundamental group. Some illustrative examples are considered.
Keywords: matematika; teorija grup; topologija